Lessons from the Auriga discs: the hunt for the Milky Way's ex situ disc is not yet over - Gómez, Facundo A.; Grand, Robert J. J.; Pakmor, Rüdiger; Simpson, Christine M.; Springel, Volker; Bustamente, Sebastian (Monthly notices of the Royal Astronomical Society, 2017)
Abstract. We characterize the contribution from accreted material to the galactic discs of the Auriga Project, a set of high-resolution magnetohydrodynamic cos